Control de Brazilian Pepper-tree - Ken Gioeli; Ken Langeland (EDIS)
SS-AGR-17-Sp, a 5-page illustrated fact sheet by Ken Gioeli and Ken Langeland, is the Spanish language version of SS-AGR-17/AA219: Brazilian Pepper Tree Control. It describes this shrub or small tree which is one of the most aggressive non-native invaders of mangrove communities and affecting nearly all terrestrial ecosystems in central and southern Florida — its history, habitat, identification, and control. Published by the UF Department of Agronomy, March 2009.